Bioactive Apigenin loaded oral nano bilosomes: Formulation optimization to preclinical assessment - Ameeduzzafar Zafar; Nabil K. Alruwaili; Syed Sarim Imam; Nasser Hadal Alotaibi; Khalid Saad Alharbi; Muhammad Afzal; Raisuddin Ali; Sultan Alshehri; Sami I. Alzarea; Mohammed Elmowafy; Nabil A. Alhakamy; Mohamed F. Ibrahim (Elsevier, 2021)
Aim: Diabetic (type-2) is a metabolic disease characterized by increased blood glucose level from the normal level. In the present study, apigenin (AG) loaded lipid vesicles (bilosomes: BIL) was prepared, optimized and evaluated for the oral therapeutic efficacy. Experimental: AG-BIL was prepared by a thin-film evaporation method using cholesterol, span 60 and sodium deoxycholate. The prepared formulation was optimized by 3-factor and 3-level Box-Behnken design using particle size, entrapment efficiency and drug release as a response. The selected formulation further evaluated for ex-vivo permeation, in vivo pharmacokinetic and pharmacodynamics study. Results: The optimized AG bilosomes (AG-BILopt) has shown the vesicle size 183.25 ± 2.43 nm, entrapment efficiency 81.67 ± 4.87%. TEM image showed a spherical shape vesicle with sharp boundaries. The drug release study revealed a significant enhancement in AG release (79.45 ± 4.18%) from AG-BILopt as compared to free AG-dispersion (25.47 ± 3.64%). The permeation and pharmacokinetic studies result revealed 4.49 times higher flux and 4.67 folds higher AUC0-t than free AG-dispersion. The antidiabetic activity results showed significant (P < 0.05) enhancement in therapeutic efficacy than free AG-dispersion. The results also showed marked improvement in biochemical parameters. Conclusion: Our findings suggested, the prepared apigenin loaded bilosomes was found to be an efficient delivery in the therapeutic efficacy in diabetes.